PERAN YAYASAN DANA PUNIA DALAM MEMBENTUK ANAK SUPUTRA - I Made Oktayama; I Gusti Ayu Suasthi; W.A. Sindhu Gitananda (WIDYANATYA, 2021)
Moral degradation is characterized by a lack of human understanding of religious teachings. Currently there are many problems that exist for children, especially those who are already teenagers. Education is divided into three types of informal, formal, and non-formal education. Character education is very necessary for children who have reached adolescence, one of which is education in foundations. Foundations have an important role in transferring the values ​​of character education so as to be able to create foster children who have noble character traits. Based on the above, there are three problems that are examined in this study, which are as follows: 1) What are the forms of attitudes of the suputra children who are trained by the Punia Fund Foundation? 2) What is the role of the Dana Punia Foundation in shaping the attitude of the suputra childrenand what are the obstacles faced by the foundation? 3) What are the implications of the role of the Dana Punia Foundation in forming suputra children ? The above problems are analyzed using behavioristic theory to dissect the first and third problems, while constructivism theory is used to dissect the formulation of the second problem.The data in this study were collected using non-participatory observation techniques, structured interview techniques and document studies, while data processing used descriptive qualitative techniques because the data were obtained from words, expressions and questions. After the data is processed, the following conclusions are obtained: 1) suputra children, namely children who have noble character, are intelligent, wise, and are proud of their family. 2) forms of suputra character education, namely religious attitudes, honesty, discipline, environmental care, creative attitudes. 3) the role of foster parents as parents, foster parents as motivators, foster parents as mentors and coaches, foster parents as facilitators. The constraints are caused by several factors, namely child factors, family factors, foster parents factors, foundation factors. 4) implications for foster children, namely increasing religious attitudes, increasing honesty, increasing disciplinary attitudes, increasing environmental care attitudes, increasing creative attitudes.